Eco-Branding Strategies and Their Impact on Consumer Buying Behavior: Evidence from SMEs in Bangladesh - Islam, Md Saiful; Segumpan, Reynaldo Gacho (Primary Journal of Multidisciplinary Research, 2025)
This study aims to analyze the impact of green marketing strategies, namely eco-branding, eco-labeling, and eco-friendly advertising, on consumer buying behavior in the Small and Medium Enterprises (SMEs) sector in Bangladesh. While awareness of sustainability is on the rise, the adoption of green marketing in Bangladesh’s SMEs is still hindered by various internal factors, such as limited resources and knowledge. Using a qualitative approach through in-depth interviews with ten respondents from sectors including textiles, apparel, and agriculture, the study reveals that eco-labeling plays a significant role in enhancing consumer trust in eco-friendly products and strengthening brand image. Eco-branding has been found to effectively foster customer loyalty by creating deeper emotional connections, while environmental advertising raises consumer awareness of sustainability, despite concerns regarding the potential for greenwashing. The study also identifies key barriers to the implementation of green marketing, including high costs, limited resources, and a lack of understanding among SME owners. It is recommended that SMEs receive further support in the form of training and government incentives to enhance the effectiveness of green marketing strategies. These findings offer valuable insights for SMEs in developing countries and policymakers, and emphasize the need for further research with larger samples and mixed methods to enrich the understanding of green marketing’s influence on consumer behavior.